DAMPAK TEKNOLOGI MODERN TERHADAP KEARIFAN LOKAL BUDAYA BATOBO DI DESA AIR TIRIS KECAMATAN KAMPAR KABUPATEN KAMPAR - ", Selvia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Basically Indonesia is a country with diverse ethnicities and cultures, the Indonesian state that is referred to as Unity which means although different but still one. One of the local culture is "Batobo" is a popular culture that there are areas, especially in the area of Riau Air Tiris Kampar district. Batobo cultural events have not been recorded or publicized being a form of local knowledge.The methods and design used in this study using quantitative research methods. Representative sampling technique performed by Yamane formula with a precision of 10% and 90% confidence level. The samples in this study were 98 persons. Based on the survey conducted in sampling the researcher decided to use accidental sampling technique is a form of nonprobability sampling in which sample members are selected based on the ease of getting taken necessary data, such as easy to find or reach. While the data analysis techniques used in this study is the Simple Linear Regression Analysis. Regression analysis was used to measure the functional relationship between two or more variables.Effect given to the indigenous culture in the village of Air Tiris batobo Kampar Kampar District by 48.0%, while the remaining 52% is influenced by other variables outside of this study. Results of simple linear regression, regression coefficient values obtained in this study is Y = 5.361 + 0.645 X. Numbers constants (a) of 5.361 and a coefficient of 0.645 with variable X t 9.413 greater than the table t 1.6605, 0.000 significance level smaller than Î± = 0:05. Based on statistical calculations were obtained, the hypothesis for this study Ha was received and Ho is rejected.Keyword: The effect of modern technology, the local wisdom, Batobo culture.